Determinants of online waqf acceptance / Hasmira Huda Hasni Fuad - Fuad, Hasmira Huda Hasni (Faculty of Business Management, University Teknologi MARA, 2018)
Waqf is defined as detention of property which are for the use and benefits of the society intended for religious or charitable purposes. Today modern Islamic charitable institutions accept monetary donations for waqf purpose and this leads to the needs of paying waq fusing internet or known as online waqf The preliminary data for this study is pilot study which have been distributed to 30 Muslims in Shah Alam area and sets of questionnaires were distributed to 300 Muslims in Shah Alam. The questionnaire sets consist of questions on both independent and dependent variables and are divided into six sections: demographic, effects of perceived usefulness, effects of perceived ease of use, effects of perceived religiosity, and effects of amount of information and acceptance on online waqf instruments. The independent variables include perceived usefulness, perceived ease of use, perceived religiosity and amount of information which will bring effects to acceptance on online waqf as the dependent variable. The researcher used Statistical Package for Social Science (SPSS) to analyse the reliability, validity, descriptive, correlation and regression analysis.